Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1148/radiol.12111580
|View full text |Cite
|
Sign up to set email alerts
|

Iliac Vein Compression as Risk Factor for Left- versus Right-Sided Deep Venous Thrombosis: Case-Control Study

Abstract: Purpose:To determine if compression of the left common iliac vein (LCIV) by the right common iliac artery is associated with left-sided deep venous thrombosis (DVT). Materials and Methods:This Results:Patients with right DVT were more likely than those with left DVT to have a history of pulmonary embolism. Overall, in all study patients, mean percentage compression was 36.6%, 66 (29.7%) of 222 had greater than 50% compression, and 16 (7.2%) had greater than 70% compression. At most levels of compression, incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
57
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 17 publications
6
57
0
1
Order By: Relevance
“…With increasingly sensitive techniques like IVUS to identify iliac compression, diagnoses are made more frequently and in a more diverse cohort of patients, yet the finding's correlation with clinical VTE is not well established . One case–control study of 230 patients demonstrated only a signal for increased left‐sided DVT when the degree of stenosis exceeded 70% of vessel diameter on CT venography …”
Section: Discussionmentioning
confidence: 99%
“…With increasingly sensitive techniques like IVUS to identify iliac compression, diagnoses are made more frequently and in a more diverse cohort of patients, yet the finding's correlation with clinical VTE is not well established . One case–control study of 230 patients demonstrated only a signal for increased left‐sided DVT when the degree of stenosis exceeded 70% of vessel diameter on CT venography …”
Section: Discussionmentioning
confidence: 99%
“…We do not confuse iliac vein compression syndrome with the original May‐Thurner description which indicates anatomical spur‐like formations at the lesion of the LCIV by the overlying RCIA . Iliac vein compression syndrome could cause left unilateral leg swelling and left‐sided deep venous thrombosis in elderly patients …”
mentioning
confidence: 86%
“…11 Furthermore, a recent case-control study suggested that compression greater than 70% is required in order to be an associated factor for left sided DVTs. 12 Although MTS has been shown to be present in about 20% of the population, it is thought to account for only 2% to 3% of all lower extremity DVTs. 10 There are over 30 known associated risk factors for the development of the initial VTE, which are classified into genetic, acquired, environmental, and mixed factors.…”
Section: Risk Factorsmentioning
confidence: 99%